استخدام الانحدار اللوجستي لدراسة أسباب إيقاف التسجيل لدى طلاب التعليم المفتوح في كلية الاقتصاد بجامعة تشرين - العشعوش أيمن (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يهدف هذا البحث إلى استخدام تقنية الانحدار اللوجستي ثنائي التصنيف لدراسة العوامل المؤثرة في ظاهرة إيقاف التسجيل لدى طلاب التعليم المفتوح في كلية الاقتصاد بجامعة تشرين، وقد تم سحب عينة عشوائية طبقية من طلاب البرامج المفتتحة في كلية الاقتصاد بحجم 339 طالباً وتم اعتماد استبانه تتضمن 15 متغيراً مستقلاً بالإضافة إلى المتغير التابع. أظهرت نتائج تقدير نموذج الانحدار اللوجستي معنوية عالية بالنسبة لمعلمات النموذج المقدرة ولجودة النموذج المستخدم ككل، وتم فرز ستة متغيرات مستقلة كأسباب محتملة لظاهرة إيقاف أو انقطاع التسجيل لدى الطلبة، وهذه المتغيرات هي: متغير الحصول على مصدقة التأجيل، متغير تأدية الخدمة الإلزامية، متغير التسجيل السابق في إحدى فروع التعليم المفتوح، متغير التواجد في بعض الأماكن غير المسيطر عليها، متغير التواجد خارج القطر، متغير ارتفاع رسوم التعليم المفتوح . The aim of this research was to use a Binary Logistic Regression Model to study the factors affecting the phenomenon of stopping enrollment of open learning students in the Faculty of Economics at Tishreen University. A random sample of students in the Faculty of Economics was randomly assigned to a total of 339 students. A questionnaire containing 15 independent variables was added in addition to the dependent variable. The results of the logistic regression model were highly significant for the parameters of the estimated model and for the goodness of fit of the model. Six independent variables were classified as possible causes of the phenomenon of discontinuation or interruption of enrollment. Obtaining a certificate of deferral for military service, performing military service, previous registration in an open education branch, housing in some places that are not controlled, presence outside the country, and high tuition fees for open learning.